Local and global well-posedness for dispersion generalized Benjamin–Ono equations on the circle. (July 2020) - Schippa, Robert
Abstract: New local well-posedness results for dispersion generalized Benjamin-Ono equations are proved in the periodic case. The family of equations under consideration links the Benjamin–Ono and Korteweg–de Vries equation. For sufficiently strong dispersion global well-posedness in L 2 ( T ) is derived.